Brassinosteroid Mediated Cell Wall Remodeling in Grasses under Abiotic Stress - Rao, Xiaolan; Dixon, Richard A. (Frontiers in Plant Science, 2017)
Unlike animals, plants, being sessile, cannot escape from exposure to severe abiotic stresses such as extreme temperature and water deficit. The dynamic structure of plant cell wall enables them to undergo compensatory changes, as well as maintain physical strength, with changing environments. Plant hormones known as brassinosteroids (BRs) play a key role in determining cell wall expansion during stress responses. Cell wall deposition differs between grasses (Poaceae) and dicots. Grass species include many important food, fiber and biofuel crops. In this article, we focus on recent advances in BR-regulated cell wall biosynthesis and remodeling in response to stresses, comparing our understanding of the mechanisms in grass species with those in the more studied dicots. A more comprehensive understanding of BR-mediated changes in cell wall integrity in grass species will benefit the development of genetic tools to improve crop productivity, fiber quality and plant biomass recalcitrance.